2022
DOI: 10.1681/asn.2022050581
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification to Predict Renal Survival in Anti–Glomerular Basement Membrane Disease

Abstract: Anti-glomerular basement membrane (GBM) disease is a rare, aggressive vasculitis with no validated prediction tools to assist its management. We investigated a retrospective multicenter international cohort with the aim to transfer the Renal Risk Score (RRS) and to identify patients that benefit from rescue immunosuppressive therapy.Of a total 191 patients, 174 patients were included in the final analysis (57% female, median age 59 years). Using Cox and Kaplan-Meier methods, the RRS was found to be a strong an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
(55 reference statements)
2
16
2
1
Order By: Relevance
“…The definition of ESKD, kidney recovery, and normal glomeruli were as follows, as described previously by Floyd et al. 15 : (i) ESKD is maintenance of RRT lasting at least 12 weeks and up to the last follow-up; (ii) kidney recovery is independence from RRT lasting at least 12 weeks during follow-up; (iii) normal glomeruli are glomeruli that did not exhibit any glomerulosclerosis, crescents, or fibrinoid necrosis. Biopsies were reviewed by an experienced nephropathologist who was blinded to the outcome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of ESKD, kidney recovery, and normal glomeruli were as follows, as described previously by Floyd et al. 15 : (i) ESKD is maintenance of RRT lasting at least 12 weeks and up to the last follow-up; (ii) kidney recovery is independence from RRT lasting at least 12 weeks during follow-up; (iii) normal glomeruli are glomeruli that did not exhibit any glomerulosclerosis, crescents, or fibrinoid necrosis. Biopsies were reviewed by an experienced nephropathologist who was blinded to the outcome.…”
Section: Methodsmentioning
confidence: 99%
“… 14 The RRS was transferred to predict kidney survival of anti-GBM disease recently by Floyd et al. 15 The authors demonstrated that combining RRT at presentation with the histological parameter of N, in the setting of the risk stratification method, might be a valuable prognostic tool for predicting ESKD in patients with anti-GBM disease. 16 Nevertheless, both models require evaluation for their predictive power regarding kidney outcomes before being widely utilized in practice.…”
mentioning
confidence: 99%
“…Dialysis dependence at admission and creatinine levels >4.7 mg/dL remained independent significant predictors of ESKD in the multivariable analysis (127). Also another study demonstrated that renal survival may be accurately predicted using a model with need for renal replacement therapy and the proportion of normal glomeruli as predictors (128). Another indicator of poor renal outcome is complement component 3 (C3).…”
Section: Outcome and Prognosismentioning
confidence: 97%
“…Antiglomerular basement membrane (Anti-GBM) disease is a rare and aggressive vasculitis characterised by the triad of rapidly progressive glomerulonephritis, pulmonary haemorrhage and the presence of circulating anti-GBM antibodies 1. Anti-GBM disease in pregnancy is an absolute rarity and the few reported cases resulted in severely preterm babies or mothers recovering from Anti-GBM disease following termination of early pregnancy 2.…”
Section: Introductionmentioning
confidence: 99%